Method for simultaneous detection and purification of chromium-containing wastewater and nano 1D COFs materials

Through the application of nano 1D COFs materials, the synchronous detection and purification of Cr(VI) in wastewater is achieved, and the problems of slow reaction speed, high cost and complex equipment in the prior art are solved, and the rapid, efficient and low-cost treatment effect is achieved, which is suitable for industrial applications.

CN119529208BActive Publication Date: 2025-04-08SOUTH CHINA UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510104285.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-08
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The prior art is difficult to realize the synchronous detection and purification of chromium-containing wastewater, and the existing methods are slow in reaction speed, high in cost and complex in equipment, making it difficult to meet the needs of industrial applications.

Method used

Using nano 1D COFs materials, the 1D COFs materials with fluorescence characteristics and porous structure are designed and synthesized through Schiff base condensation reaction, so as to achieve rapid detection and efficient removal of Cr(VI) in wastewater. The material supports the synchronization of detection and purification steps through fluorescence reaction and catalyzed reduction reaction of oxalic acid.

Benefits of technology

It realizes rapid detection and efficient removal of Cr(VI) in wastewater, with fast processing speed, high efficiency, low cost, simple process, can meet the industry's multi-faceted demand for chromium-containing wastewater and is easy to promote and apply on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529208B_ABST
    Figure CN119529208B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of wastewater treatment and heavy metal detection, and discloses a method for simultaneous detection and purification of chromium-containing wastewater and a nano 1D COFs material, the method comprising the following steps: S1, preparing a green fluorescent nano covalent organic framework 1D COFs material; S2, chromium-containing wastewater detection, using a fluorescence quenching method to quickly detect the concentration of hexavalent chromium (Cr(VI)) in the water body; S3, chromium-containing wastewater purification, adding an organic acid reducing agent oxalic acid, using 1D COFs as a catalyst, efficiently removing Cr(VI) from the water body, and completing the simultaneous detection and purification of chromium-containing wastewater. The present invention also provides a nano 1D COFs material that extends and grows in only one direction to form a linear structure linked by a covalent bond, specifically C‑COF and O‑COF, which can achieve simultaneous rapid detection and efficient removal of Cr(VI) in water bodies, meeting industrialization needs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment and heavy metal detection, and in particular to a method for simultaneous detection and purification of chromium-containing wastewater and a nano 1D COFs material. Background Art

[0002] Existing studies have shown that as one of the important trace nutrients in the human body, chromium (Cr) is an important blood sugar regulator and a component of protease, and plays an important role in the body's glucose and lipid metabolism and protein synthesis. Chromium mainly exists in two valence states: trivalent chromium (Cr(III)) and hexavalent chromium (Cr(VI)). The toxicity of chromium is related to its valence state. Cr(VI) is 100 times more toxic than Cr(III), and is easily absorbed and accumulated in the body, seriously endangering human health. The main sources of chromium pollution include wastewater discharged from the processing of chromium-containing ores, metal surface treatment, leather tanning, printing and dyeing, etc.

[0003] At present, conventional detection methods for Cr(VI) rely on large instruments that are not easy to carry and can only be performed in laboratories, such as inductively coupled plasma mass spectrometry and atomic absorption spectroscopy. The detection and purification steps are separated from each other, so the cost of detection and purification is high and cannot be commercially applied. Fluorescence detection is considered to be a promising Cr(VI) detection method due to its advantages of high sensitivity, good selectivity and good portability. However, it can only complete one link of detection and cannot achieve simultaneous removal of Cr(VI).

[0004] At present, common methods for removing Cr(VI) include chemical reduction, physical adsorption, electroreduction, membrane filtration, photocatalysis, etc. These methods require long-term adsorption and complex operation and equipment, and do not have detection capabilities by themselves. They must also be used in conjunction with some complex Cr(VI) sampling and detection instruments. Therefore, how to quickly and simultaneously detect and remove Cr(VI) in wastewater remains a huge technical challenge.

[0005] In the prior art, the organic acid oxalic acid (OA) is usually discharged in industrial wastewater together with heavy metals and dyes. It is known that the carboxyl group in OA can expand the coordination number of Cr(VI) to drive the reduction process, but the reduction process is very slow. Therefore, some researchers have also mediated the reduction of Cr(VI) with oxalic acid by adding goethite, alumina, and clay minerals, but the treatment time is still long and the catalytic efficiency is low. Other studies in the prior art have shown that under the action of light, existing conventional mediators can convert OA into reducing free radicals (·CO 2- ), but a light environment must be provided. Therefore, the reduction reaction has high requirements on the chromaticity, suspended solids and other indicators of Cr(VI) wastewater, which leads to great restrictions on the use conditions of this method and is difficult to apply industrially.

[0006] The covalent organic frameworks (COF) of the prior art, referred to as COF, are a new type of crystalline organic porous materials linked by covalent bonds. Due to their unique physical and chemical properties, they have been studied and applied in adsorption separation, biomedicine, sensing, catalysis, optics, etc. There are many types of COF. If they are divided according to the dimension, they can be divided into three-dimensional COF, two-dimensional COF and one-dimensional COF. Generally speaking, a three-dimensional COF can be obtained by continuously extending in three directions to form a three-dimensional network, and a two-dimensional COF can be obtained by extending in two directions to form a two-dimensional planar network. The two-dimensional COF planes are usually stacked to form a one-dimensional nanochannel; for most three-dimensional and two-dimensional COF divisions, the synthesized COF is the same as the number of dimensions of the constructed unit, but this method is not applicable to the definition of one-dimensional COF provided by the present invention. The present invention application defines a framework material that only extends and grows in one direction to form a linear structure linked by covalent bonds as a one-dimensional COF material, i.e., 1D COF.

[0007] In summary, the existing technology has separate steps for the detection and purification of chromium-containing wastewater, and must rely on different instruments, equipment and materials; the existing purification treatment uses oxalic acid to reduce Cr(VI), which has a slow reaction rate and high requirements; the catalytic effect of conventional catalytic materials is poor, requiring light, and the catalytic materials can only be used for catalytic reduction reactions, and cannot be used to detect the concentration of Cr(VI) in wastewater at the same time. In other words, the existing technology and materials cannot achieve the simultaneous detection and purification of Cr(VI) in wastewater, and cannot meet the industry's requirements for simple, low-cost, and high-efficiency processes for the detection and purification of chromium-containing wastewater. Summary of the invention

[0008] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to propose a method for simultaneous detection and purification of chromium-containing wastewater and a nano 1D COFs material. Through the simultaneous improvement of components, proportions and processes, two framework 1D COFs materials that extend and grow in only one direction to form a linear structure linked by covalent bonds are obtained, and the material has fluorescent properties and a large number of coral-like stacked nano-papillaries and porous structures, which can support the simultaneous detection and purification steps of Cr(VI) in wastewater, without the need for complex instruments and processes, and the detection and purification of Cr(VI) in wastewater are fast, efficient, effective, low-cost, and simple in process. It can simultaneously meet the industry's various needs for detection and purification of chromium-containing wastewater and is easy to promote and apply on a large scale.

[0009] The present invention provides the following technical solutions to achieve the above-mentioned purpose:

[0010] A method for simultaneous detection and purification of chromium-containing wastewater, comprising the following steps:

[0011] S1. Preparation of green fluorescent nano-covalent organic framework 1D COFs materials

[0012] Preparation of a framework material that only extends and grows in one direction to form a linear structure linked by covalent bonds, which has a 1D double-chain structure, a highly symmetrical zigzag shape, and a coral-like stacked porous and nanoscale papillary structure of one-dimensional green fluorescent nano-covalent organic framework 1D COFs materials, including C-COF and O-COF;

[0013] S2. Detection of chromium-containing wastewater

[0014] The green fluorescent nano covalent organic framework material 1D COF material is prepared into a dispersion, wastewater containing Cr(VI) is added into the dispersion, and the concentration of Cr(VI) in the wastewater is rapidly detected by the fluorescence quenching method;

[0015] S3. Purification of chromium-containing wastewater

[0016] According to the concentration of Cr(VI) in the water sample obtained by detection, the corresponding proportion of catalyst 1D COFs material and raw material oxalic acid are added. With its microstructure and physical and chemical properties, this material can quickly catalyze the reduction reaction of oxalic acid and efficiently remove Cr(VI) in the water, thus completing the simultaneous detection and purification of chromium-containing wastewater.

[0017] A nano 1D COFs material is used to implement the method for simultaneous detection and purification of chromium-containing wastewater. It is a framework 1D COFs material that extends and grows in only one direction to form a linear structure linked by covalent bonds and has a large number of nano-papillae and diamond-shaped channel structures, specifically a green fluorescent covalent organic framework, 1D structured C-COF and O-COF; the material simultaneously performs rapid detection and efficient removal of Cr(VI) in water through a fluorescent reaction with Cr(VI) and a catalytic reduction reaction of oxalic acid.

[0018] Compared with the existing technology, the present invention has the following advantages and effects:

[0019] 1. The method for simultaneous detection and purification of chromium-containing wastewater and the nano 1D COFs material provided by the present invention focus on the problems of detection and purification separation of Cr(VI) in wastewater in the prior art, and through the simultaneous improvement of components, proportions and processes, two framework 1D COFs materials are obtained that extend and grow in only one direction to form a linear structure linked by covalent bonds, and the material has fluorescent properties and a nano stacked papilla structure, which can support the simultaneous detection and purification (catalysis) steps of Cr(VI) in wastewater, without the need for complex instruments and processes, and the detection and purification treatment is fast, efficient, effective, and low in cost. It can simultaneously meet the industry's various needs for detection and purification of chromium-containing wastewater and is easy to promote and apply on a large scale.

[0020] 2. The nano 1D COFs material and preparation method provided by the present invention adopt a highly symmetrical C4 monomer and a typical "V"-shaped monomer to design and synthesize a highly symmetrical, zigzag one-dimensional (1D) covalent organic framework (COF) material that grows in only one direction through a Schiff base condensation reaction; and based on the Zig-Zag close-packed structure presented between the 1D-COFs chains, additional non-covalent interactions are introduced between the strip frameworks, so that the 1D COFs exhibit low-density basal sites and more edge active sites on their skeletons, which can effectively improve the exposure of active sites and ultimately increase the chemically active surface area. In addition, the double-chain structure of the 1D configuration of the material can enhance the directionality of electron transfer, thereby reducing the energy loss during exciton dissociation. In the preparation method provided by the present invention, the successful construction of the one-dimensional structural material depends on specific nonlinear connectors. These connectors have a typical "V" shape with an opening angle ranging from 90° to 150°, which is conducive to the formation of a serrated 1D configuration by covalently connecting high-symmetry C4 building blocks under harsh reaction conditions, and ultimately constructing a 1D material with a unique nano-stacked porous micromorphology.

[0021] 3. The nano 1D COFs material and its preparation method provided by the present invention, by precisely controlling the components and processes, makes it extend and grow in only one direction, forming a linear structure linked by covalent bonds, and has a large number of nano-papillae and rhombus pore structures. Compared with the framework interaction brought by π-π stacking in 2D-COFs, the AIEgens located at the framework nodes in the 1D-COFs material will significantly enhance its restricted intramolecular rotation (Restricted Intramolecular Rotation, RIR) effect due to the additional limiting effect, thereby significantly enhancing the photoluminescence performance of the 1D-COFs material. The present invention characterizes the morphology, specific surface area, functional groups and fluorescent catalytic performance of the material by using different means, and conducts actual experiments. The results all show that the unique microstructure and physical and chemical properties of the material enable it to be applied to the simultaneous treatment of detection and purification of Cr(VI)-containing wastewater.

[0022] 4. The present invention adopts the highly symmetrical C4 fluorescent monomer tetrakis-(4-formyl-(1,1-biphenyl))ethylene with aggregation-induced luminescence and "V"-shaped monomers 4,4'-diaminodiphenylmethane and 4,4'-diaminodiphenyl ether and other components to prepare two 1D COFs materials with coral-like nano-papillae and channels through Schiff base condensation reaction; in the preparation process, through the coordination of multiple steps, the Schiff base condensation reaction is utilized to make the 1D-COFs chain extend and grow in only one direction, and finally form two framework 1D COFs materials with a linear structure linked by covalent bonds; the preparation method has fewer overall steps, simple process, easy control of reaction conditions, and is easy to industrialize and produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of the reaction route for preparing C-COF and O-COF according to an embodiment of the present invention;

[0024] Figure 2 SEM images of C-COF and O-COF prepared in the examples of the present invention, wherein a is C-COF and b is O-COF;

[0025] Figure 3 XRD patterns of C-COF and O-COF prepared in the examples of the present invention, wherein a is C-COF and b is O-COF;

[0026] Figure 4 TEM and element mapping images of C-COF prepared in the embodiment of the present invention, wherein a is a TEM image of C-COF at 500nm, b is a dark field morphology image of C-COF, c is a C element mapping image, and d is a N element mapping image;

[0027] Figure 5 TEM and element mapping images of O-COF prepared in the embodiment of the present invention, wherein a is a TEM image of O-COF at 500nm, b is a dark field morphology image of O-COF, c is a C element mapping image, d is a N element mapping image, and e is an O element mapping image;

[0028] Figure 6 EDS graphs of C-COF and O-COF prepared in the examples of the present invention, wherein a is the EDS graph of C-COF, and b is the EDS graph of O-COF;

[0029] Figure 7 The XPS graphs of C-COF and O-COF prepared in the examples of the present invention, wherein a is the full XPS spectrum of C-COF, and b is the full XPS spectrum of O-COF;

[0030] Figure 8 Thermogravimetric diagrams of C-COF and O-COF prepared in the embodiment of the present invention, wherein a is the thermogravimetric diagram of C-COF, and b is the thermogravimetric diagram of O-COF;

[0031] Fig. 9 Nitrogen adsorption-desorption curves a, c, and pore size distribution diagrams b, d of C-COF and O-COF prepared in the embodiment of the present invention, wherein a is the nitrogen adsorption-desorption curve of C-COF, b is the nitrogen adsorption-desorption curve of O-COF, c is the pore size distribution diagram of C-COF, and d is the pore size distribution diagram of O-COF;

[0032] Fig.10 The excitation and emission spectra comparison diagram of C-COF and O-COF prepared in the embodiment of the present invention, wherein a is the excitation and emission spectrum of C-COF dispersion (λex=438 nm), and the inset is the daylight and fluorescence photos of C-COF dispersion (λex=365 nm); b is the excitation and emission spectrum of O-COF dispersion (λex=468 nm), and the inset is the daylight and fluorescence photos of O-COF dispersion (λex=365 nm);

[0033] Fig.11 This is a comparison diagram of the effects of different metal ions on the fluorescence of C-COF and O-COF prepared in an embodiment of the present invention, wherein a is a comparison diagram of the effects of C-COF (λex = 438 nm); b is a comparison diagram of the effects of O-COF (λex = 468 nm);

[0034] Fig.12Schematic diagram of fluorescence stability comparison of C-COF and O-COF prepared in an embodiment of the present invention, wherein a is intra-batch stability (C-COF); b is inter-batch stability (C-COF); c is fluorescence stability within 7 days (C-COF); d is reproducibility (C-COF); e is intra-batch stability (O-COF); f is inter-batch stability (O-COF); g is fluorescence stability within 7 days (O-COF); h is reproducibility (O-COF);

[0035] Fig.13 Optimization diagram of detection conditions for C-COF and O-COF prepared in the embodiment of the present invention, wherein a is the optimization of solvent for C-COF dispersion; b is the optimization of concentration for C-COF dispersion; c is the optimization of mixing time for C-COF dispersion and Cr(VI) (λex = 438 nm, c = 50 μmol / L); d is the optimization of solvent for O-COF dispersion; e is the optimization of concentration for O-COF dispersion; f is the optimization of mixing time for O-COF dispersion and Cr(VI) (λex = 468 nm, c = 50 μmol / L);

[0036] Fig.14 The linear relationship diagram of C-COF and O-COF prepared in the embodiment of the invention for Cr(VI) detection, wherein a is the fluorescence spectrum of Cr(VI) solution with different concentrations added to C-COF dispersion (λex=438 nm); b is the standard curve for Cr(VI) detection; c is the fluorescence spectrum of Cr(VI) solution with different concentrations added to O-COF dispersion (λex=468 nm); d is the standard curve for Cr(VI) detection;

[0037] Fig.15 The interference effects of other ions and organic matter that may coexist in C-COF and O-COF prepared in the embodiments of the invention on Cr(VI), wherein a is the effect of other ions or organic matter on the detection of Cr(VI) by C-COF (λex=438 nm, c=50 μmol / L); b is the effect of other ions or organic matter on the detection of Cr(VI) by O-COF (λex=468 nm, c=50 μmol / L);

[0038] Fig.16 This is a comparison chart of the Cr(VI) removal capabilities of different reaction systems of C-COF and O-COF materials prepared in an embodiment of the present invention, wherein a is a chart of the Cr(VI) removal capabilities of different reaction systems of C-COF materials; b is a chart of the Cr(VI) removal capabilities of different reaction systems of O-COF materials;

[0039] Fig.17Schematic diagram of the effect of the concentration of C-COF and O-COF prepared in an embodiment of the present invention on the catalytic reduction of Cr(VI), wherein a is a schematic diagram of the effect of the concentration of C-COF on the catalytic reduction of Cr(VI); b is a schematic diagram of the effect of the concentration of O-COF on the catalytic reduction of Cr(VI);

[0040] Fig.18 Schematic diagram of the effect of OA addition on Cr(VI) catalytic reduction in an embodiment of the present invention, wherein a is a schematic diagram of the effect of OA addition on Cr(VI) catalytic reduction under a C-COF catalytic system; b is a schematic diagram of the effect of OA addition on Cr(VI) catalytic reduction under an O-COF catalytic system;

[0041] Fig.19 The figure shows the reduction effect of OA catalyzed by C-COF and O-COF prepared in the embodiments of the present invention on the Cr(VI) solution prepared from real water and deionized water, wherein a is the reduction effect of C-COF catalyzed by OA on the Cr(VI) solution prepared from real water and deionized water, and b is the reduction effect of OA catalyzed by O-COF on the Cr(VI) solution prepared from real water and deionized water. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0043] Basic Example

[0044] A method for simultaneous detection and purification of chromium-containing wastewater, comprising the following steps:

[0045] S1. Preparation of green fluorescent nano-covalent organic framework 1D COFs materials

[0046] Preparation of a framework material that only extends and grows in one direction to form a linear structure linked by covalent bonds, which has a 1D double-chain structure, a highly symmetrical zigzag shape, and a coral-like stacked porous and nanoscale papillary structure of one-dimensional green fluorescent nano-covalent organic framework 1D COFs materials, including C-COF and O-COF;

[0047] S2. Detection of chromium-containing wastewater

[0048] The green fluorescent nano covalent organic framework material 1D COF material is prepared into a dispersion, wastewater containing Cr(VI) is added into the dispersion, and the concentration of Cr(VI) in the wastewater is rapidly detected by the fluorescence quenching method;

[0049] S3. Purification of chromium-containing wastewater

[0050] According to the concentration of Cr(VI) in the water sample obtained by detection, the corresponding proportion of catalyst 1D COFs material and raw material oxalic acid are added. With its microstructure and physical and chemical properties, this material can quickly catalyze the reduction reaction of oxalic acid and efficiently remove Cr(VI) in the water, thus completing the simultaneous detection and purification of chromium-containing wastewater.

[0051] A nano 1D COFs material, which is used to implement the aforementioned method for simultaneous detection and purification of chromium-containing wastewater. It is a framework 1D COFs material that extends and grows in only one direction to form a linear structure linked by covalent bonds and has a large number of nano-papillae and pore structures, specifically a green fluorescent covalent organic framework, 1D structured C-COF and O-COF; the material can rapidly detect and efficiently remove Cr(VI) in water in situ through a fluorescent reaction with Cr(VI) and a catalytic reduction reaction of oxalic acid.

[0052] The following is combined with Figure 1-19 , which is described in detail with multiple specific embodiments.

[0053] Example 1

[0054] The method for simultaneous detection and purification of chromium-containing wastewater and nano 1D COFs material provided in this embodiment are based on the basic embodiment and specifically prepare C-COF powder.

[0055] Preparation of nano 1D COFs material C-COF powder, see Figure 1 , is prepared by using a highly symmetrical C4 fluorescent monomer tetrakis-(4-formyl-(1,1-biphenyl))ethylene (ETBA) and a "V"-shaped monomer 4,4'-diaminodiphenylmethane (MDA) through a Schiff base condensation reaction, specifically using the following steps:

[0056] S1-1-1: Tetrakis-(4-formyl-(1,1-biphenyl)ethylene (ETBA), 4,4-diaminodiphenylmethane (MDA), o-dichlorobenzene, and n-butanol were added to a 5 mL Pyrex tube in sequence. After ultrasonication for 15 min, acetic acid aqueous solution was added, and liquid nitrogen freezing and degassing operations were performed three times to achieve vacuum oxygen-free conditions in the reaction system.

[0057] The molar ratio of tetrakis-(4-formyl-(1,1-biphenyl)ethylene to 4,4-diaminodiphenylmethane is 1:2; the molar amount of tetrakis-(4-formyl-(1,1-biphenyl)ethylene is 0.016-0.032 mmol; the molar amount of 4,4-diaminodiphenylmethane (MDA) is 0.032-0.064 mmol;

[0058] The volume ratio of o-dichlorobenzene to n-butanol is 1:(1-4);

[0059] The volume of the added acetic acid aqueous solution is 0.1-0.2 mL, and the concentration is 6-9 mol / L;

[0060] The specific selections in this embodiment are:

[0061] The amount of substance of tetrakis-(4-formyl-(1,1-biphenyl)ethylene was 0.016 mmol;

[0062] The amount of substance of 4,4-diaminodiphenylmethane was 0.032 mmol;

[0063] The volume ratio of o-dichlorobenzene to n-butanol is 1:4, and the dosage is 0.2 mL:0.8 mL;

[0064] The amount of 6 mol / L acetic acid aqueous solution added was 0.12 mL.

[0065] S1-1-2: After the degassed Pyrex tube is thawed naturally, it is placed in an oven and heated to 100-120°C, then maintained at 120°C for reaction. After 120 hours of reaction, the oven is closed and allowed to cool naturally to room temperature;

[0066] S1-1-3: Collect the product obtained in step S1-1-1 by filtration, wash with methanol and tetrahydrofuran respectively, and then wash with acetone by centrifugation three times each;

[0067] S1-1-4: Finally, tetrahydrofuran and acetone Soxhlet extraction were used for solvent exchange. After the solvent was evaporated in a vacuum drying oven at 80°C for 24 hours (ensuring that the solvent was completely evaporated), a 1D COFs material C-COF was obtained, which extended and grew in only one direction to form a linear framework linked by covalent bonds, and was a yellow powder.

[0068] Example 2

[0069] The method for simultaneous detection and purification of chromium-containing wastewater and nano 1D COFs material provided in this embodiment specifically prepares C-COF powder, which is substantially the same as that in Example 1, except that:

[0070] In step S1-1-1 of this embodiment, the specific selection is:

[0071] The amount of substance of tetrakis-(4-formyl-(1,1-biphenyl)ethylene was 0.025 mmol;

[0072] The amount of substance of 4,4-diaminodiphenylmethane was 0.05 mmol;

[0073] The volume ratio of o-dichlorobenzene and n-butanol is 1:1, and the dosage is 0.5 mL:0.5 mL;

[0074] The amount of 9 mol / L acetic acid aqueous solution added was 0.1 mL;

[0075] S1-1-2: After the degassed Pyrex tube is thawed naturally, it is placed in an oven and heated to 120-140°C, then maintained at 140°C for reaction. After 90 hours of reaction, the oven is closed and allowed to cool naturally to room temperature;

[0076] S1-1-3: Collect the product obtained in step S1-1-1 by filtration, wash with methanol and tetrahydrofuran respectively, and then wash with acetone by centrifugation three times each;

[0077] S1-1-4: Finally, tetrahydrofuran and acetone Soxhlet extraction were used for solvent exchange. After evaporating the solvent in a vacuum drying oven at 60°C for 30 hours (ensuring that the solvent was completely evaporated), a 1D COFs material C-COF was obtained, which extended and grew in only one direction to form a linear framework linked by covalent bonds, and was a yellow powder.

[0078] Example 3

[0079] The method for simultaneous detection and purification of chromium-containing wastewater and nano 1D COFs materials provided in this embodiment specifically prepares C-COF powder, which is substantially the same as that of Embodiment 1 and Embodiment 2, except that:

[0080] In step S1-1-1 of this embodiment, the specific selection is:

[0081] The amount of substance of tetrakis-(4-formyl-(1,1-biphenyl)ethylene was 0.032 mmol;

[0082] The amount of substance of 4,4-diaminodiphenylmethane was 0.064 mmol;

[0083] The volume ratio of o-dichlorobenzene to n-butanol is 1:3, and the dosage is 0.25 mL:0.75 mL;

[0084] The amount of 6 mol / L acetic acid aqueous solution added was 0.1 mL.

[0085] S1-1-2: After the degassed Pyrex tube is thawed naturally, it is placed in an oven and heated to 140-150°C, then maintained at 150°C for reaction. After 72 hours of reaction, the oven is closed and allowed to cool naturally to room temperature;

[0086] S1-1-3: Collect the product obtained in step S1-1-1 by filtration, wash with methanol and tetrahydrofuran respectively, and then wash with acetone by centrifugation three times each;

[0087] S1-1-4: Finally, tetrahydrofuran and acetone Soxhlet extraction were used for solvent exchange. After evaporating the solvent in a vacuum drying oven at 70°C for 48 hours (ensuring that the solvent was completely evaporated), a 1D COFs material C-COF was obtained, which extended and grew in only one direction to form a linear framework linked by covalent bonds, and was a yellow powder.

[0088] Example 4

[0089] The method for simultaneous detection and purification of chromium-containing wastewater and nano 1D COFs material provided in this embodiment are based on the basic embodiment and specifically prepare O-COF powder.

[0090] Preparation of nano 1D COFs material O-COF powder, see Appendix Figure 1 , is prepared by using highly symmetrical C4 fluorescent monomers tetrakis-(4-formyl-(1,1-biphenyl))ethylene (ETBA) and 4,4'-diaminodiphenyl ether (ODA) through Schiff base condensation reaction, specifically using the following steps:

[0091] S1-2-1: Tetrakis-(4-formyl-(1,1-biphenyl)ethylene (ETBA), 4,4'-diaminodiphenyl ether (ODA), o-dichlorobenzene, and n-butanol were added to a 5 mL Pyrex tube in sequence. After ultrasonication for 15 min, acetic acid aqueous solution was added, and liquid nitrogen freezing and degassing operations were performed three times to achieve vacuum oxygen-free conditions in the reaction system.

[0092] Among them, the molar ratio of tetrakis-(4-formyl-(1,1-biphenyl)ethylene and 4,4'-diaminodiphenyl ether is 1:2; the concentration of tetrakis-(4-formyl-(1,1-biphenyl)ethylene is 0.016-0.032 mmol; the concentration of 4,4'-diaminodiphenyl ether (ODA) is 0.032-0.064 mmol;

[0093] The volume ratio of o-dichlorobenzene to n-butanol is 1:(1-4);

[0094] The concentration of acetic acid aqueous solution is 6-9 mol / L, and the amount added is 0.1-0.2 mL;

[0095] In step S1-2-1 of this embodiment, the specific selection is:

[0096] The amount of substance of tetrakis-(4-formyl-(1,1-biphenyl)ethylene was 0.016 mmol;

[0097] The amount of substance of 4,4'-diaminodiphenyl ether was 0.032 mmol;

[0098] The volume ratio of o-dichlorobenzene to n-butanol is 1:4, and the dosage is 0.2 mL:0.8 mL;

[0099] The amount of 6 mol / L acetic acid aqueous solution added was 0.12 mL.

[0100] S1-2-2: After the degassed Pyrex tube is naturally thawed, it is placed in an oven and first heated to 100-120°C, then maintained at 120°C for reaction. After 120 hours of reaction, the oven is closed and allowed to cool naturally to room temperature;

[0101] S1-2-3: Filter and collect the product obtained in step S1-2-2, wash it with methanol and tetrahydrofuran respectively, and then centrifuge and wash it with acetone three times each;

[0102] S1-2-4: Finally, tetrahydrofuran and acetone Soxhlet extraction were used for solvent exchange. After evaporating the solvent in a vacuum drying oven at 60°C for 72 hours (ensuring that the solvent was completely evaporated), a 1D COFs material O-COF was obtained, which extended and grew in only one direction to form a linear framework linked by covalent bonds, in the form of a yellow powder.

[0103] Example 5

[0104] The method for simultaneous detection and purification of chromium-containing wastewater and nano 1D COFs materials provided in this embodiment specifically prepares O-COF powder, which is substantially the same as that in Example 4, except that:

[0105] In step S1-1-1 of this embodiment, the specific selection is:

[0106] The amount of substance of tetrakis-(4-formyl-(1,1-biphenyl)ethylene was 0.025 mmol;

[0107] The amount of substance of 4,4'-diaminodiphenyl ether (ODA) was 0.05 mmol;

[0108] The volume ratio of o-dichlorobenzene and n-butanol is 1:1, and the dosage is 0.5 mL:0.5 mL;

[0109] The amount of 9 mol / L acetic acid aqueous solution added was 0.1 mL;

[0110] S1-2-2: After the degassed Pyrex tube is thawed naturally, it is placed in an oven and heated to 120-140°C, then maintained at 140°C for reaction. After 90 hours of reaction, the oven is closed and allowed to cool naturally to room temperature;

[0111] S1-2-3: Filter and collect the product obtained in step S1-2-2, wash it with methanol and tetrahydrofuran respectively, and then centrifuge and wash it with acetone three times each;

[0112] S1-2-4: Finally, tetrahydrofuran and acetone Soxhlet extraction were used for solvent exchange. After the solvent was evaporated in a vacuum drying oven at 70°C for 48 hours, a 1D COFs material O-COF was obtained, which extended and grew in only one direction to form a linear framework linked by covalent bonds, in the form of a yellow powder.

[0113] Example 6

[0114] The method for simultaneous detection and purification of chromium-containing wastewater and nano 1D COFs materials provided in this embodiment specifically prepares O-COF powder, which is substantially the same as that of Embodiment 4 and Embodiment 5, except that:

[0115] In step S1-1-1 of this embodiment, the specific selection is:

[0116] The amount of substance of tetrakis-(4-formyl-(1,1-biphenyl)ethylene was 0.032 mmol;

[0117] The amount of substance of 4,4'-diaminodiphenyl ether (ODA) was 0.064 mmol;

[0118] The volume ratio of o-dichlorobenzene to n-butanol is 1:3, and the dosage is 0.25 mL:0.75 mL;

[0119] The amount of 6 mol / L acetic acid aqueous solution added was 0.1 mL;

[0120] S1-2-2: After the degassed Pyrex tube is thawed naturally, it is placed in an oven and heated to 140-150°C, then maintained at 150°C for reaction. After 72 hours of reaction, the oven is closed and allowed to cool naturally to room temperature;

[0121] S1-2-3: Filter and collect the product obtained in step S1-2-2, wash it with methanol and tetrahydrofuran respectively, and then centrifuge and wash it with acetone three times each;

[0122] S1-2-4: Finally, tetrahydrofuran and acetone Soxhlet extraction were used for solvent exchange. After the solvent was evaporated in a vacuum drying oven at 80°C for 24 hours, a 1D COFs material O-COF was obtained, which extended and grew in only one direction to form a linear framework linked by covalent bonds, in the form of a yellow powder.

[0123] The crystal form, morphology, specific surface area, element distribution and thermal stability of the C-COF prepared in Examples 1 to 3 and the O-COF materials prepared in Examples 4 to 6 were studied by XRD, SEM, TEM, EDS, XPS and TGA. Because the various shapes of the C-COF prepared in Examples 1 to 3 and the O-COF materials prepared in Examples 4 to 6 are similar, in order to avoid repetition, only the materials prepared in Examples 1 and 4 are described as representatives.

[0124] First, the morphology of the C-COF prepared in Example 1 and the O-COF prepared in Example 4 was studied by SEM characterization. Figure 2 ,in, Figure 2 Figure a is a SEM image of C-COF, which exhibits a double-chain structure with a 1D configuration, a highly symmetrical serrated shape, and a coral-like stacked porous and nanoscale papillary structure at the micrometer scale. The overall outline is a coral-like stacked block particle.

[0125] Figure 2 Figure b is an SEM image of O-COF, which exhibits a double-chain structure with a 1D configuration, a highly symmetrical serrated shape, and a coral-like stacked porous and nanoscale papillae structure at the micrometer scale. The overall outline is coral-like stacked cone particles. The difference in the microscopic morphology between C-COF and O-COF is due to different components and elements, but both have a large number of nano-papillaries and channels.

[0126] The morphologies of the two materials were studied by SEM and TEM. Figure 2 It can be seen that C-COF and O-COF present similar double-chain structures, highly symmetrical serrated shapes, and coral-like stacked porous and nanoscale nipple structures, respectively, and the sizes of their nipples and pores range widely from 500 nm to 1 μm; the specific morphologies of the two materials, C-COF and O-COF, are basically similar, with some differences due to the different raw material component elements used.

[0127] See also Figure 3The morphologies of C-COF and O-COF materials were studied by XRD characterization. It was found that the obvious diffraction peaks of C-COF material at 4.5°, 6.5°, 9.0°, 14.5°, 18.1° and 19.7° were attributed to the (110), (200), (220), (420), (001) and (211) crystal planes; the obvious diffraction peaks of O-COF material at 4.5°, 6.5°, 9.1°, 14.9°, 18.3° and 20.0° were attributed to the (110), (200), (220), (001), (111) and (311) crystal planes. The results show that both C-COF and O-COF materials have good crystal forms. Figure 3 XRD characterization shows that both C-COF and O-COF have typical characteristic peaks at 4.5°, which belong to the (110) crystal plane. The results show that both materials have good crystal forms. Further XPS characterization shows that C and N elements exist in C-COF materials, and C, N, and O elements exist in O-COF materials.

[0128] from Figure 4 and Figure 5 From the HR-TEM images, we can observe the existence of lattice fringes in C-COF and O-COF, indicating that the two materials have two rows of crystal forms; at the same time, the element distribution mapping diagram shows that the C and N elements in C-COF are evenly distributed in the COF skeleton, and the C, N, and O elements in O-COF are evenly distributed in the COF skeleton.

[0129] observe Figure 6 EDS analysis and Figure 7 XPS analysis shows that C, N and C, N, O elements exist in both COF materials, which is consistent with the element distribution mapping characterization.

[0130] Depend on Figure 8 The thermogravimetric analysis results show that the thermogravimetric curves of the two COFs materials remain basically unchanged in the temperature range of 30°C to 500°C. When the temperature continues to rise to 800°C, their thermogravimetric curves begin to decrease, indicating that both materials have excellent thermal stability.

[0131] In addition, the BET surface areas and intrinsic pores of C-COF and O-COF were determined by nitrogen adsorption and desorption experiments at 77 K. Fig. 9 .observe Fig. 9 The nitrogen adsorption-desorption curves (a, c) and pore size distribution diagrams (b, d) of C-COF and O-COF show that the specific surface areas of C-COF and O-COF materials are 630 m 3 / g and 590 m 3 / g, and the pore size is mainly distributed within 10 nm, indicating that the material is a nano-scale mesoporous material. The nitrogen adsorption-desorption curve shows the characteristics of a type II adsorption isotherm and has an H3 type hysteresis loop, which is consistent with the physical property of the COF material with a larger pore structure.

[0132] See attached Fig.10 In this embodiment, the fluorescence properties of C-COF and O-COF materials are tested by fluorescence spectroscopy. Fig.10 As shown in Figure a, the maximum excitation and emission wavelengths of C-COF are 438 nm and 495 nm, respectively. Fig.10 As shown in b, under daylight conditions, C-COF is yellow in color. When irradiated with a fluorescent lamp with an excitation light of 365 nm, C-COF exhibits uniform green fluorescence. The maximum excitation and maximum emission wavelengths of O-COF are 468 nm and 520 nm, respectively. Under daylight conditions, O-COF is yellow in color. When irradiated with a fluorescent lamp with an excitation light of 365 nm, O-COF exhibits uniform green fluorescence.

[0133] See attached Fig.11 , the fluorescence selectivity of C-COF and O-COF materials was studied by fluorescence spectroscopy characterization, and some heavy metal ions were selected for testing to examine the selectivity of 1D COFs (C-COF and O-COF) for common heavy metals. The specific steps are: take a certain mass of the above different metal ions, and prepare them into sample solutions with a concentration of 1.0 mmol / L for use; take 2.5 mL of the prepared green COFs material dispersion and place it in the sample cell of the fluorescence spectrophotometer for scanning, and perform a second scan when the cuvette concentration is 50 μmol / L. The generated fluorescence signal is detected by the detector and the change in fluorescence intensity before and after the addition of the COFs material is recorded. The results obtained are shown in Fig.11 , where a is a C-COF material and b is an O-COF material. Fig.11 It can be seen that when Cs is added + , Pb 2+ , Mn 2+ 、Ni 2+ Mg 2+ , Fe 2+ 、Co 2+ Cr 3+ 、Al 3+ ,Th 4+ , U 6+ There is no obvious fluorescence change, and the F0 / F-1 response value caused by Cr(VI) is the largest. This result shows that the two 1D COFs materials can selectively recognize Cr(VI).

[0134] This example also tests the fluorescence stability of 1D COFs materials. The fluorescence stability of C-COF and O-COF dispersions prepared in the same batch was studied. The results are shown in Fig.12 As shown in a and e in the figure, the dispersions prepared in the same batch were measured 9 times, and the RSD of the fluorescence intensity values ​​was less than 1.6%, indicating that the C-COF and O-COF dispersions prepared in the same batch have good fluorescence stability. Fig.12 As shown in Figures b and f, the RSDs of the fluorescence intensity values ​​of C-COF and O-COF dispersions prepared in 9 different batches were all less than 2.4%, indicating that C-COF and O-COF dispersions had good fluorescence stability. Fig.12 As shown in c and g in Figure , the fluorescence intensity of C-COF and O-COF dispersions remained basically unchanged within 7 days, and the RSD of the fluorescence intensity values ​​within 7 days was less than 1.8%; Fig.12 As shown in Figures d and h, the reproducibility of C-COF and O-COF dispersions to Cr(VI) was further investigated. It was found that the responses of C-COF and O-COF dispersions to Cr(VI) were basically consistent in the seven times, indicating that both C-COF and O-COF dispersions have good reproducibility to Cr(VI).

[0135] Example 7

[0136] This embodiment uses a one-dimensional covalent organic framework nanomaterial 1D COFs as a fluorescent sensor to quickly detect Cr(VI), and then performs simultaneous purification in situ. Specifically, the C-COF and O-COF materials prepared in Example 1 and Example 4 are respectively applied to the simultaneous detection and purification of chromium-containing wastewater, which includes the following steps:

[0137] S2. Detection of chromium-containing wastewater

[0138] The green fluorescent nano covalent organic framework material 1D COF material prepared in Example 1 and Example 4 was respectively prepared into a dispersion liquid, wastewater containing Cr(VI) was added to the dispersion liquid, and the concentration of Cr(VI) in the wastewater was quickly detected by fluorescence quenching method;

[0139] S2-1: respectively adding C-COF or O-COF material to the dispersion to prepare a suspension of a set concentration, and recording the fluorescence intensity F0 of the fluorescent substance before contacting the sample solution to be detected;

[0140] The dispersion solution is a phosphate buffer solution with a concentration of 0.2 mmol / L and a pH of 7;

[0141] S2-2: After the Cr(VI) solutions of varying standard concentrations are contacted with the suspension and reacted for a time of not less than 6 seconds, the fluorescence intensity F generated by the reaction of the 1D COFs material with the Cr(VI) solutions of varying standard concentrations is recorded, and the value of the linear equation F0 / F-1 of the degree of change in fluorescence intensity is calculated to obtain a comparison chart of the linear equation F0 / F-1 value of the degree of change in Cr(VI) concentration and the degree of change in fluorescence quenching of the 1D COFs material;

[0142] In this embodiment, 2.5 mL of the pre-prepared C-COF or O-COF material suspension is taken, placed in a cuvette, and 0.2-300 μmol / L of different concentrations of Cr(VI) are added, and then the corresponding data is obtained by fluorescence spectrum test, the change of fluorescence intensity F before and after the reaction is detected, and the standard curve in the comparison chart is drawn;

[0143] S2-3: A solution of the sample to be tested containing Cr(VI) is added to the suspension. After the contact and reaction time is not less than 6 s, the fluorescence intensity F generated by the fluorescent substance after the reaction is recorded;

[0144] S2-4: Calculate the value of the linear equation F0 / F-1, and then compare it with the standard curve to obtain the concentration value of Cr(VI) in the sample solution to be tested containing Cr(VI).

[0145] This example further tests the optimization conditions for 1D COFs detection of Cr(VI), and finds that the dispersion solvent, dispersion concentration, and mixing time all have important effects on the detection of Cr(VI). Fig.13 As shown in a and d, when the dispersion solvent is selected as water, PBS, ethanol, methanol and DMF, the fluorescence response (F0 / F-1) value of PBS dispersion of C-COF and O-COF is the largest, so PBS is selected as the solvent dispersion; Fig.13 As shown in Figure b, when the concentration of C-COF dispersion increases from 0.05 mg / mL to 0.25 mg / mL, the F0 / F-1 value increases first and then decreases with the concentration. The reason for this phenomenon may be that with the increase in concentration, the contact sites between C-COF and Cr(VI) increase; when the concentration of the dispersion is too high, precipitation will occur. Therefore, the concentration of C-COF dispersion was selected as 0.05 mg / mL for the following fluorescence experiments. Fig.13As shown in Figure e, when the concentration of O-COF dispersion increases from 0.05 mg / mL to 0.1 mg / mL, the F0 / F-1 value increases. When the concentration of O-COF dispersion increases from 0.1 mg / mL to 0.25 mg / mL, the F0 / F-1 value increases first and then decreases with the concentration. The reason for this phenomenon may be that with the increase in concentration, the contact sites between O-COF and Cr(VI) increase. Therefore, the concentration of O-COF dispersion was selected as 0.1 mg / mL for the subsequent fluorescence experiment. Finally, the mixing time of C-COF and O-COF dispersions with Cr(VI) was optimized, as shown in Figure 5. Fig.13 As shown in Figures c and f, when the mixing time is in the range of 3 to 6 s, the F0 / F-1 value increases, and as time continues to increase, the F0 / F-1 value remains basically unchanged; the reason may be that the C-COF and O-COF dispersions are fully in contact with Cr(VI) within 6 s, so the mixing treatment time of C-COF and O-COF dispersions with Cr(VI) can be selected as 6 s.

[0146] Based on the fact that Cr(VI) can cause fluorescence quenching of 1D COFs (C-COF and O-COF), a fluorescence analysis method for Cr(VI) was established based on this property. The linear response of C-COF and O-COF materials to Cr(VI) was studied by fluorescence spectroscopy characterization. The steps are as follows: Cr(VI) standard solutions with concentrations of 0.2, 0.5, 2.0, 5.0, 10.0, 15.0, 20.0, 30.0, 50.0, 100.0, 150.0, 200.0, and 300.0 μmol / L were prepared for use; the COFs material dispersion was placed in the sample cell of a fluorescence spectrophotometer for scanning, and the fluorescence spectrum intensity F0 was recorded; the COFs material was fully contacted with Cr(VI) standard solutions of different concentrations, and then placed in the sample cell of a fluorescence spectrophotometer for scanning, and the fluorescence spectrum intensity F was recorded. The linear equation of the fluorescence quenching degree F0 / F-1 of the COFs material and different concentrations of Cr(VI) was obtained through data processing.

[0147] The fluorescence spectra of the 1D COFs material after reacting with Cr(VI) dispersions of different concentrations are shown in Fig.14 , where a and b are the linear correspondence of the Cr(VI) concentration of the C-COF material, and c and d are the linear correspondence of the Cr(VI) concentration of the O-COF material. Fig.14 As shown in a and c in Figure 1, as the concentration of Cr(VI) solution increases, the quenching degree increases, and the fluorescence intensity of C-COF and O-COF dispersions begins to gradually quench, and it is found that the fluorescence peak position does not move. Fig.14As shown in (b), when the Cr(VI) concentration is 0.2-300.0 μmol / L, C-COF and Cr(VI) concentration show good linearity, and the linear regression equation is F0 / F-1= 0.01+0.01x, and the linear correlation coefficient R 2 =0.9987, and the detection limit (S / N=3) is 78 nmol / L. Fig.14 As shown in (d), when the Cr(VI) concentration is 0.5-300.0 μmol / L, O-COF and Cr(VI) concentration show good linearity, and the linear regression equation is F0 / F-1=0.006+0.012x, and the linear correlation coefficient R 2 =0.9931, and the detection limit (S / N=3) was 175 nmol / L.

[0148] See attached Fig.15 In this example, the anti-interference performance of 1D COFs materials in fluorescence spectroscopy detection was studied. C-COF and O-COF were used to study the anti-interference performance of Cr(VI) by fluorescence spectroscopy characterization. Inorganic ions and organic matter that may coexist in water environment samples were selected for testing, including OH - , Cl - 、SO4 2- , K + 、Na + Mg 2+ , starch, glucose, D-fructose, L-lysine, L-tryptophan. Fig.15 As shown in a and b, when interfering substances were added to the Cr(VI) solutions containing 50.0 μmol / L respectively, the change rates of the fluorescence signals of C-COF and O-COF were both less than 10%, indicating that these inorganic ions and organic matter that may coexist in the water environment have little interference with the detection results of Cr(VI) of 1D COFs materials.

[0149] S3. Purification of chromium-containing wastewater

[0150] According to the concentration of Cr(VI) in the water sample detected, a corresponding proportion of catalyst C-COF or O-COF material and an organic acid reducing agent oxalic acid are added. The microstructure and physical and chemical properties of the material can quickly catalyze the reduction reaction of oxalic acid, effectively remove Cr(VI) in the water in situ, and complete the simultaneous detection and purification of chromium-containing wastewater to obtain ideal purification efficiency and effect, including:

[0151] S3-1: According to the concentration of Cr(VI) in the water sample detected in step S2, the amount of 1DCOFs catalyst and organic acid reducing agent oxalic acid (OA) to be added is calculated respectively;

[0152] S3-2: Add the required 1D COFs material and the organic acid reducing agent oxalic acid into the water body and stir continuously to promote the full progress of the catalytic reduction reaction;

[0153] S3-3: Sample the water in the reaction at regular intervals, and then measure the concentration of Cr(VI) in each sample of water obtained at each time point until the ideal Cr(VI) removal effect is achieved, and then stop stirring.

[0154] This example evaluates the catalytic reduction performance of C-COF and O-COF. The designed preliminary experiment uses C-COF and O-COF materials as catalysts, selects the organic acid reducing agent oxalic acid (OA) to carry out catalytic reduction experiments on Cr(VI) in water, and evaluates the removal ability of 1DCOFs materials for Cr(VI) under the catalytic OA reduction system. The experimental steps are as follows: add 10 mL of 50 mg / L Cr(VI) solution to two 20 mL sample bottles, and then add 4 mg C-COF material, 10 mg oxalic acid, 4 mg O-COF material and 10 mg oxalic acid to different sample bottles, place the sample bottles in a constant temperature shaking incubator, react at a speed of 160 rpm and 30°C for 2 hours, take samples regularly to determine the Cr(VI) concentration, and set up only OA and only COF material systems as controls.

[0155] The preliminary experimental results are as follows Fig.16 As shown in the figure, both adding COF material and adding OA alone can remove a certain amount of Cr(VI). The system adding OA alone showed significant fluctuation in the removal of Cr(VI). The system adding C-COF alone can remove Cr(VI) with a certain regularity. The system adding O-COF alone also showed fluctuation in the removal of Cr(VI). The C-COF-catalyzed OA system achieved a Cr(VI) removal efficiency of 95.8% within 30 min (see Fig.16 In a), the O-COF-catalyzed OA system achieved a Cr(VI) removal efficiency of 97.7% within 30 min (see Fig.16 Both showed excellent removal performance.

[0156] The single factor effect study was further conducted with the pre-experimental reaction parameters as a reference. The remaining reaction parameters were fixed to test the effects of different O-COF concentrations, OA addition amounts, and reaction temperatures on the removal of Cr(VI).

[0157] First, the effect of C-COF and O-COF material concentrations on Cr(VI) removal was investigated. When the C-COF and O-COF concentrations were 5-15 mg / L, the Cr(VI) removal efficiency was faster within 60 min of reaction. Fig.17 As shown in a, they are 97.7%, 98.9% and 98.2% respectively; the removal efficiency of O-COF for Cr(VI) is shown in Fig.17 As shown in (b), they are 98.7%, 99.0% and 99.0% respectively. The Cr(VI) removal efficiency gradually increases with the increase of C-COF and O-COF material concentrations until it slightly decreases at 15 mg / L. The above phenomenon shows that 1D COFs material systems with different concentrations have relatively ideal Cr(VI) removal effects.

[0158] The Cr of C-COF was studied with 2.5-10 mg OA addition. 6+ Removal experiment, Cr within 60 min 6+ The removal rates were 81.0%, 96.3%, 97.0% and 97.0% respectively (e.g. Fig.18 a); 5-15 mg OA was added to perform Cr 6+ Removal experiment, Cr within 60 min 6+ The removal rates were 87.7%, 96.3%, 96.3% and 96.3% respectively (e.g. Fig.18 (b) The removal effect of the C-COF reaction system showed a trend of rising and then falling, indicating that oxalic acid as an electron donor had a significant impact on the catalytic performance of the system.

[0159] Example 8

[0160] In this embodiment, based on the embodiment 7, the C-COF and O-COF materials prepared in the embodiments 1 and 4, respectively, are actually applied to the simultaneous detection and purification of actual chromium-containing wastewater samples.

[0161] The fluorescence spectrometry established by the 1DCOFs material system was used to detect Cr(VI) in samples of lake water, tap water, and soil solution collected in the actual environment, and a spike recovery experiment was performed. From Table 1 (C-COF and O-COF spike recovery experiment table in fluorescence spectrometry, actual sample detection (n=3)), it can be seen that the recovery rate obtained by C-COF is 92.7%-109.7%, and the relative standard error is less than 5%; the recovery rate obtained by O-COF is 93.4%-112.8%, and the relative standard error is less than 8%. It shows that the results of the detection and purification of Cr(VI) by the fluorescence detection and purification method established in the embodiment of the present invention are accurate and reliable.

[0162] Table 1

[0163]

[0164] Note: a: Recovery rate (%) = 100 × (test concentration / spiked concentration); b: RSD is relative standard error.

[0165] See also Fig.19 In this example, the C-COF and O-COF materials prepared in the above-mentioned examples 1 and 4 were used as catalysts, respectively, and the organic acid reducing agent oxalic acid (OA) was used to carry out a catalytic reduction experiment on Cr(VI) in the actual sampled water. The experimental steps are as follows: The Cr(VI) removal system in Example 7 was constructed according to a mass ratio of 1 / 100 of COF material (0.1 mg) to OA (10 mg), and deionized water was used to prepare an equal concentration of Cr(VI) solution to carry out a removal capacity comparison test according to the same reaction system as above. Among them, the removal rate of C-COF for Cr(VI) in the actual sampled water was 96.2% (such as Fig.19 In a), the removal rate of Cr(VI) in the actual sampled water by O-COF was 95.5% ( Fig.19 In b), the removal rate error of the water sample prepared with deionized water is within 0.01%. It can be seen that the COF material prepared by the present invention has good environmental adaptability and is minimally affected by the comprehensive influence of environmental conditions.

[0166] The method for simultaneous detection and purification of chromium-containing wastewater and the green fluorescent nano covalent organic framework 1D COFs material provided by the embodiment of the present invention enable the detection and purification methods to be carried out simultaneously in situ; the preparation method of the 1D COFs material has simple steps, easy-to-control process conditions, and is easy to mass produce. After actual application tests, the 1DCOFs material and the simultaneous detection and purification method provided by the present invention have broad application prospects in the field of chromium-containing wastewater detection and treatment, and can meet the application needs of industrialization.

[0167] It should be noted that in other embodiments of the present invention, other different schemes obtained by making specific selections within the scope of the steps, components, ratios, process parameters and conditions recorded in the present invention can all achieve the technical effects recorded in the present invention, so the present invention will no longer list them one by one.

[0168] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. All equivalent changes made according to the components, proportions and processes of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for simultaneous detection and purification of chromium-containing wastewater, characterized in that: The steps include: S1. Preparation of green fluorescent nano-covalent organic framework 1D COFs materials Preparation of a framework material that only extends and grows in one direction to form a linear structure linked by covalent bonds. It has a 1D double-chain structure, a highly symmetrical zigzag shape, and a coral-like stacked porous and nanoscale papillary structure. One-dimensional green fluorescent nano-covalent organic framework 1D COFs material is one of C-COF or O-COF; C-COF is a yellow powdery material prepared by a Schiff base condensation reaction of a highly symmetrical C4 fluorescent monomer tetrakis-(4-formyl-(1,1-biphenyl))ethylene and a "V"-shaped monomer 4,4'-diaminodiphenylmethane. O-COF is a yellow powdery material prepared by Schiff base condensation reaction of highly symmetrical C4 fluorescent monomers tetrakis-(4-formyl-(1,1-biphenyl))ethylene and 4,4'-diaminodiphenyl ether. S2. Detection of chromium-containing wastewater Two green fluorescent nano covalent organic framework materials 1D COF materials, either C-COF or O-COF, are prepared into a dispersion, wastewater containing Cr(VI) is added into the dispersion, and the concentration of Cr(VI) in the wastewater is rapidly detected by fluorescence quenching method; S3. Purification of chromium-containing wastewater According to the concentration of Cr(VI) in the water sample obtained by detection, the corresponding proportion of catalyst 1D COFs material and reducing agent oxalic acid are added. With its microstructure and physical and chemical properties, this material can quickly catalyze the reduction reaction of oxalic acid and efficiently remove Cr(VI) in the water, thus completing the simultaneous detection and purification of chromium-containing wastewater.

2. The method for simultaneous detection and purification of chromium-containing wastewater according to claim 1, characterized in that: In the step S1, the C-COF step S1-1 in the 1D COFs is prepared by using a highly symmetrical C4 fluorescent monomer tetrakis-(4-formyl-(1,1-biphenyl))ethylene and a "V"-shaped monomer 4,4'-diaminodiphenylmethane through a Schiff base condensation reaction, specifically using the following steps: S1-1-1: Tetrakis-(4-formyl-(1,1-biphenyl)ethylene and 4,4-diaminodiphenylmethane, o-dichlorobenzene, and n-butanol are sequentially added to a Pyrex tube, and an acetic acid aqueous solution is added after ultrasonication, and three liquid nitrogen freezing and degassing operations are performed to achieve vacuum oxygen-free conditions in the reaction system; S1-1-2: After the degassed Pyrex tube is thawed naturally, it is placed in an oven and heated to 100-150°C for reaction. After reacting for 72-120 hours, the oven is closed and the tube is allowed to cool naturally to room temperature; S1-1-3: Collect the product obtained in step S1-1-1 by filtration, wash with methanol and tetrahydrofuran respectively, and then wash with acetone by centrifugation three times each; S1-1-4: Finally, tetrahydrofuran and acetone were used for Soxhlet extraction and solvent exchange, and the mixture was kept in a vacuum drying oven at 60-80°C for 24-72 hours. After evaporation of the solvent, a 1D COFs material C-COF in the form of a yellow powder was obtained, which grew in only one direction and formed a linear framework structure linked by covalent bonds.

3. The method for simultaneous detection and purification of chromium-containing wastewater according to claim 2, characterized in that In step S1-1-1, the molar ratio of tetrakis-(4-formyl-(1,1-biphenyl)ethylene to 4,4-diaminodiphenylmethane is 1:2; The volume ratio of o-dichlorobenzene to n-butanol is 1:(1-4); Add 6-9 mol / L acetic acid aqueous solution in an amount of 10%-20% of the total volume of o-dichlorobenzene and n-butanol.

4. The method for simultaneous detection and purification of chromium-containing wastewater according to claim 1, characterized in that: In the step S1, the step S1-2 of preparing the O-COF in 1D COFs is specifically performed by the following steps: S1-2-1: Tetrakis-(4-formyl-(1,1-biphenyl)ethylene (ETBA), 4,4'-diaminodiphenyl ether (ODA), o-dichlorobenzene, and n-butanol are sequentially added to a Pyrex tube, and an acetic acid aqueous solution is added after ultrasonication, and a liquid nitrogen freeze degassing operation is performed to obtain a vacuum oxygen-free condition of the reaction system; S1-2-2: After the degassed Pyrex tube is naturally thawed, it is placed in an oven and heated to 100-150°C for reaction. After reacting for 72-120 hours, the oven is closed and the tube is naturally cooled to room temperature; S1-2-3: Filter and collect the product obtained in step S1-2-2, and wash it three times by centrifugation with methanol, tetrahydrofuran and acetone respectively; S1-2-4: Finally, tetrahydrofuran and acetone were used for Soxhlet extraction and solvent exchange, and the mixture was kept in a vacuum drying oven at 60-80°C for 24-72 hours. After the solvent was evaporated, a 1D COFs material O-COF in the form of a yellow powder was obtained, which grew in only one direction and formed a linear framework structure linked by covalent bonds.

5. The method for simultaneous detection and purification of chromium-containing wastewater according to claim 4, characterized in that The molar ratio of tetrakis-(4-formyl-(1,1-biphenyl)ethylene to 4,4'-diaminodiphenyl ether in S1-2-1 is 1:2; The volume ratio of o-dichlorobenzene to n-butanol is 1:(1-4); Add 6-9 mol / L acetic acid aqueous solution in an amount of 10%-20% of the total volume of o-dichlorobenzene and n-butanol.

6. The method for simultaneous detection and purification of chromium-containing wastewater according to claim 1, characterized in that: The step S2 of chromium-containing wastewater detection specifically comprises the following steps: S2-1: Add 1D COFs material to the dispersion to prepare a suspension, and record the fluorescence intensity F0 of the fluorescent substance before contacting the sample solution to be detected; S2-2: After the Cr(VI) solution with varying standard concentrations is contacted with the suspension and reacted for a time of not less than 6 s, the fluorescence intensity F generated by the reaction of the 1D COFs material with the Cr(VI) solution with varying standard concentrations is recorded, and the value of the linear equation F0 / F-1 of the degree of change in fluorescence intensity is calculated to obtain a comparison chart of the linear equation F0 / F-1 value of the degree of change in Cr(VI) concentration and the degree of change in fluorescence quenching of the 1D COFs material; S2-3: A solution of the sample to be tested containing Cr(VI) is added to the suspension. After the contact and reaction time is not less than 6 s, the fluorescence intensity F generated by the fluorescent substance after the reaction is recorded; S2-4: Calculate the value of the linear equation F0 / F-1, and then compare it with the standard curve to obtain the concentration value of Cr(VI) in the sample solution to be tested containing Cr(VI).

7. The method for simultaneous detection and purification of chromium-containing wastewater according to claim 6, characterized in that The dispersion in step S2-1 is a phosphate buffer solution with a concentration of 0.2 mmol / L and a pH of 7; The step S2-2 is to take 2.5 mL of the 1D COFs material suspension, place it in a cuvette, add 0.2~300 μmol / L of different concentrations of Cr(VI), and then use fluorescence spectroscopy to obtain corresponding data, detect the change in fluorescence intensity F before and after the reaction, and draw a standard curve in the control chart.

8. The method for simultaneous detection and purification of chromium-containing wastewater according to claim 1, characterized in that The step S3 of purifying chromium-containing wastewater specifically comprises the following steps: S3-1: According to the concentration of Cr(VI) in the water sample detected in step S2, the amount of oxalic acid, a reducing agent, and the amount of 1D COFs catalyst to be added are calculated respectively; S3-2: Add the reducing agent oxalic acid and the 1D COFs to be supplemented into the water body, and continue stirring to promote the full progress of the catalytic reduction reaction; S3-3: Sample the water in the reaction at regular intervals, and then measure the concentration of Cr(VI) in the water samples obtained at each time point until the ideal Cr(VI) removal effect is achieved, and then stop stirring.